Mothers' satisfaction with referral hospital delivery service in Amhara Region, Ethiopia - Tayelgn Azmeraw; Zegeye Desalegn T; Kebede Yigzaw (BMC, 2011)
Abstract Background A woman's satisfaction with the delivery service may have immediate and long-term effects on her health and subsequent utilization of the services. Providing satisfying delivery care increases service utilization. The objective of this study is to assess the satisfaction of mothers with referral hospitals' delivery service and identify some possible factors affecting satisfaction in Amhara region of Ethiopia. Methods A hospital-based cross-sectional survey that involved an exit interview was conducted from September to November 2009 in three referral hospitals in Ethiopia. A total of 417 delivering mothers were enrolled in the study. Client satisfaction was measured using a survey instrument adopted from the Donabedian quality assessment framework. We collect data systematically from every other postnatal woman who delivered in the referral hospitals. Multivariate and binary logistic regression was applied to identify the relative effect of each explanatory variable on the outcome (satisfaction). Results The proportion of mothers who were satisfied with delivery care in this study was 61.9%. Women's satisfaction with delivery care was associated with wanted status of the pregnancy, immediate maternal condition after delivery, waiting time to see the health worker, availability of waiting area, care providers' measure taken to assure privacy during examinations, and amount of cost paid for service. Conclusions The overall satisfaction of hospital delivery services in this study is found to be suboptimal. The study strongly suggests that more could be done to assure that services provided are more patient centered.